Microbiome Dynamics and Functional Composition in Coelopa frigida (Diptera, Coelopidae): Insights into Trophic Specialization of Kelp Flies - Bischof, Paul S. P.; Bartolomaeus, Theda U. P.; Löber, Ulrike; Bleidorn, Christoph (Microbial ecology, 2024)
Coelopidae (Diptera), known as kelp flies, exhibit an ecological association with beached kelp and other rotting seaweeds. This unique trophic specialization necessitates significant adaptations to overcome the limitations of an algal diet. We aimed to investigate whether the flies’ microbiome could be one of these adaptive mechanisms. Our analysis focused on assessing composition and diversity of adult and larval microbiota of the kelp fly Coelopa frigida . Feeding habits of the larvae of this species have been subject of numerous studies, with debates whether they directly consume kelp or primarily feed on associated bacteria. By using a 16S rRNA metabarcoding approach, we found that the larval microbiota displayed considerably less diversity than adults, heavily dominated by only four operational taxonomic units (OTUs). Phylogenetic placement recovered the most dominant OTU of the larval microbiome, which is the source of more than half of all metabarcoding sequence reads, as an undescribed genus of Orbaceae (Gammaproteobacteria). Interestingly, this OTU is barely found among the 15 most abundant taxa of the adult microbiome, where it is responsible for less than 2% of the metabarcoding sequence reads. The other three OTUs dominating the larval microbiome have been assigned as Psychrobacter (Gammaproteobacteria), Wohlfahrtiimonas (Gammaproteobacteria), and Cetobacterium (Fusobacteriota). Moreover, we also uncovered a distinct shift in the functional composition between the larval and adult stages, where our taxonomic profiling suggests a significant decrease in functional diversity in larval samples. Our study offers insights into the microbiome dynamics and functional composition of Coelopa frigida .